Your highness [videorecording (DVD)] - McBride, Danny, 1976-; McBride, Danny, 1976-; Best, Ben; Franco, James, 1978-; Portman, Natalie, 1981-; Deschanel, Zooey, 1980-; Theroux, Justin; Jones, Toby, 1966-; Lewis, Damian, 1971-; Jablonsky, Steve; Webb-Crozier, Hazel; Orr, Tim (Universal Studios Home Entertainment, 2011)
Two royal princes, slacker, weed-smoking Thadeous and the noble Fabious, join with an elusive warrior on a quest to free a princess from an evil wizard. Along the way, they'll have to vanquish horrific creatures and traitorous knights.